Ab initio electronic structure and optical conductivity of bismuth tellurohalides - Schwalbe, Sebastian; Wirnata, René; Starke, Ronald; Schober, Giulio Albert Heinrich; Kortus, Jens (Physical review, 2016)
We investigate the electronic structure, dielectric, and optical properties of bismuth tellurohalides BiTeX (X=I, Cl, Br) by means of all-electron density functional theory. In particular, we present the ab initio conductivities and dielectric tensors calculated over a wide frequency range, and compare our results with the recent measurements by Akrap et al. [Phys. Rev. B 90, 035201 (2014)], Makhnev et al. [Opt. Spectrosc. 117, 764 (2014)], and Rusinov et al. [JETP Lett. 101, 507 (2015)]. We show how the low-frequency branch of the optical conductivity can be used to identify characteristic intra- and interband transitions between the Rashba spin-split bands in all three bismuth tellurohalides. We further calculate the refractive indices and dielectric constants, which in turn are systematically compared to previous predictions and measurements. We expect that our quantitative analysis will contribute to the general assessment of bulk Rashba materials for their potential use in spintronics devices.